TNB-486 induces potent tumor cell cytotoxicity coupled with low cytokine release in preclinical models of B-NHL - Harbani K. Malik-Chaudhry; Kirthana Prabhakar; Harshad S. Ugamraj; Andrew A. Boudreau; Benjamin Buelow; Kevin Dang; Laura M. Davison; Katherine E. Harris; Brett Jorgensen; Heather Ogana; Duy Pham; Ute Schellenberger; et al. (Taylor & Francis Group, 2021)
The therapeutic potential of targeting CD19 in B cell malignancies has garnered attention in the past decade, resulting in the introduction of novel immunotherapy agents. Encouraging clinical data have been reported for T cell-based targeting agents, such as anti-CD19/CD3 bispecific T-cell engager blinatumomab and chimeric antigen receptor (CAR)-T therapies, for acute lymphoblastic leukemia and B cell non-Hodgkin lymphoma (B-NHL). However, clinical use of both blinatumomab and CAR-T therapies has been limited due to unfavorable pharmacokinetics (PK), significant toxicity associated with cytokine release syndrome and neurotoxicity, and manufacturing challenges. We present here a fully human CD19xCD3 bispecific antibody (TNB-486) for the treatment of B-NHL that could address the limitations of the current approved treatments. In the presence of CD19+ target cells and T cells, TNB-486 induces tumor cell lysis with minimal cytokine release, when compared to a positive control. In vivo, TNB-486 clears CD19+ tumor cells in immunocompromised mice in the presence of human peripheral blood mononuclear cells in multiple models. Additionally, the PK of TNB-486 in mice or cynomolgus monkeys is similar to conventional antibodies. This new T cell engaging bispecific antibody targeting CD19 represents a novel therapeutic that induces potent T cell-mediated tumor-cell cytotoxicity uncoupled from high levels of cytokine release, making it an attractive candidate for B-NHL therapy.